Anther and pollen development in barley - Fernández, José (2012)
The control of pollen viability and release is of major commercial importance in the development of crops for hybrid seed production and selective breeding. It has been shown that key transcription factors in Arabidopsis particularly MALE STERILITY1 (MS1), are functionally conserved in rice (Li et al., 2011), therefore extending this comparative analysis and controlling fertility in temperate cereals, such as barley, is the long term goal of this project.